A modified organic silicon polymer material and preparation method thereof
By mixing silicone polymer with modified silica, modified silicone polymer materials are prepared, which solves the problem of aging of silicone polymer materials under environmental factors, and achieves the anti-aging and self-repairing effect of the material, extends the service life and reduces pollution.
Patent Information
- Application Number
- CN202411186816.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-28
AI Technical Summary
Silicone polymer materials are prone to aging under the influence of environmental factors such as ultraviolet rays, heat, and oxygen, resulting in reduced physical and mechanical properties, affecting service life and causing waste of resources and environmental pollution.
Modified silicone polymer is prepared by mixing the silicone polymer with the modified silica. Modified silica is prepared by reacting with 3-aminopropyltrimethoxysilane, 3-aldehyde-4-hydroxybenzoate and sodium hydroxide, and has the ability to absorb ultraviolet rays; silicone polymer is prepared by reactions of self-healing monomers, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, formaldehyde and glyoxal, and has the ability to self-heal.
Modified silicone polymer materials show good anti-aging and self-healing capabilities under aging conditions, extending service life, reducing resource waste and environmental pollution, and improving the wear resistance of the materials.
Smart Images

Figure 7X73W0E7MEPPZZF3WDVWA4GJZB4HISFUCLZDGCU3 
Figure HZP9K3GHDA2JIZ8M9VSKSIOQITIJBFKE95IRNBCY 
Figure TNJJLDYVXX1LJR3M4OGBLVGXIJZ0ZLVEJ77DJCSC
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a modified organic silicon polymer material and a preparation method thereof. Background Art
[0002] The polymer containing silicon in the molecular structure and one or more organic groups connected to the silicon atom is called organosilicon polymer. According to the different types of other atoms connected to the silicon atom, there are polysilane, polysiloxane, polysilazane, polysilocarbazine, etc. Among them, polysiloxane is a kind of polymer whose main chain is composed of repeated silicon-oxygen bonds, and the side chains are connected to organic groups, such as methyl groups. It is the most common and widely used type of polymer in organosilicon polymer materials.
[0003] However, during use, silicone polymer materials are often affected by environmental factors such as ultraviolet rays, heat, and oxygen, causing irreversible aging reactions, resulting in reduced physical properties, such as hardening, brittleness, loss of gloss, bending and deformation, silver streaks, cracks, and decreased mechanical properties, thereby affecting the service life of the polymer material. Due to its wide application, it can also cause waste of resources and environmental pollution. Therefore, this article introduces an aging-resistant modified silicone polymer material. Summary of the invention
[0004] The purpose of the present invention is to provide a modified organic silicon polymer material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] A modified organic silicon polymer material, wherein the modified organic silicon polymer material is obtained by uniformly mixing an organic silicon polymer and modified silicon dioxide;
[0006] The modified silicon dioxide is prepared by reacting silicon dioxide with 3-aminopropyltrimethoxysilane, 3-formyl-4-hydroxybenzoic acid methyl ester and sodium hydroxide in sequence;
[0007] The organosilicon polymer is prepared by reacting a self-repairing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, formaldehyde and glyoxal;
[0008] The self-repairing monomer is prepared by sequentially reacting 4-vinylbenzeneboronic acid with 3,4-dihydroxy-1-butene and 3-mercapto-1-propylamine.
[0009] A method for preparing a modified organic silicon polymer material, the method for preparing the modified organic silicon polymer material mainly comprises the following preparation steps:
[0010] (1) Mix amino silica, methyl 3-formyl-4-hydroxybenzoate and ethanol in a mass ratio of 1:1:10-12, stir at 200-300 rpm for 20-30 min, filter, wash, and dry at 70-80 ° C for 6-8 h to obtain pre-modified silica; mix pre-modified silica, deionized water and sodium hydroxide in a mass ratio of 1:5-7:0.08-0.1, stir at 200-300 rpm for 20-30 min, filter, wash, and dry at 80-90 ° C for 10-12 h to obtain modified silica;
[0011] (2) Mix boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate in a mass ratio of 735-745:40-42:1:48-52, stir at 200-300 rpm and 24-26°C for 22-26 hours, filter the filtrate, and dry to obtain boric acid ester; mix boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile in a molar ratio of 1:2:6-8:0.01-0.02, stir at 68-72°C and 200-300 rpm for 3-4 hours, and dry to obtain a self-healing monomer;
[0012] (3) The aldehyde mixture is uniformly added to the ammonia mixture within 8 to 10 minutes, reacted at 24 to 26°C and 25 to 35 rpm for 5 to 7 hours, and vacuum dried at 55 to 65°C for 4 to 6 hours to obtain an organosilicon polymer; the organosilicon polymer and modified silica are stirred at 200 to 300 rpm for 20 to 30 minutes to obtain an organosilicon polymer material.
[0013] As an optimization, the preparation method of the amino silica in step (1) is to uniformly mix nano-silica, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 1:1~2:8~10, stir the mixture at 85~95°C and 200~300rpm for 5~7h, centrifuge, wash with deionized water for 3~5 times, and dry at 90~100°C for 2~4h.
[0014] As an optimization, the specific operation method of the washing in step (1) is to wash with deionized water 3 to 5 times.
[0015] As an optimization, the boric acid dispersion in step (2) is prepared by mixing 4-vinylbenzeneboric acid and tetrahydrofuran in a mass ratio of 2-4:69-73 and ultrasonicating for 20-30 minutes.
[0016] As an optimization, the specific operation method of the drying in step (2) is vacuum drying at 80-100°C for 22-24 hours.
[0017] As an optimization, the ammonia mixed liquid in step (3) is prepared by uniformly mixing self-repairing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, methanol, oxalic acid and glacial acetic acid in a mass ratio of 4~6:30~40:3~5:235~239:0.6~0.7:5~6.
[0018] As an optimization, the aldehyde mixture in step (3) is prepared by uniformly mixing formaldehyde and glyoxal in a molar ratio of 1:1.
[0019] As an optimization, the preparation process of the self-repairing monomer in step (2) is as follows:
[0020] .
[0021] As an optimization, the reaction mechanism of the amino group with formaldehyde and glyoxal in step (3) is as follows:
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] When preparing the modified organic silicon polymer material, the present invention sequentially reacts silicon dioxide with 3-aminopropyltrimethoxysilane, 3-aldehyde-4-hydroxybenzoic acid methyl ester and sodium hydroxide to obtain the modified silicon dioxide; sequentially reacts 4-vinylbenzeneboronic acid with 3,4-dihydroxy-1-butene and 3-mercapto-1-propylamine to obtain a self-repairing monomer; the self-repairing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, formaldehyde and glyoxal are reacted to obtain an organic silicon polymer; and the organic silicon polymer and the modified silicon dioxide are uniformly mixed to obtain the modified organic silicon polymer material.
[0024] Firstly, silica is reacted with 3-aminopropyltrimethoxysilane, 3-formyl-4-hydroxybenzoic acid methyl ester and sodium hydroxide in sequence to obtain modified silica; 4-vinylphenylboronic acid is reacted with 3,4-dihydroxy-1-butene and 3-mercapto-1-propylamine in sequence to obtain a self-healing monomer; nano-silica can enhance the wear resistance of the material, and the reaction of amino-silica and 3-formyl-4-hydroxybenzoic acid methyl ester can generate a structure with the ability to absorb ultraviolet rays, thereby achieving an anti-aging effect; then reacting with sodium hydroxide, the ester on the benzene ring is hydrolyzed to form a carboxyl anion, which can achieve a better binding effect with the imidazolium ion contained in the subsequently generated polyester; boric acid ester can achieve a self-healing effect at high temperature.
[0025] Secondly, the self-repairing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, formaldehyde and glyoxal are reacted to obtain an organosilicon polymer, and the organosilicon polymer is uniformly mixed with modified silicon dioxide to obtain a modified organosilicon polymer material. The self-repairing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, formaldehyde and glyoxal can react to generate imidazolium ions, which can exert pharmacological activity by inhibiting the synthesis of DNA and RNA. They can bind to existing enzymes and change the conformation of the enzymes, thereby blocking the extension of nucleic acid chains. They can also act as enzyme inhibitors to inhibit specific enzyme activities. In addition, imidazolium ions can interfere with the exchange of substances inside and outside cells by changing the permeability of cell membranes, causing them to lose nutrients and water, and leading to the death of bacteria and fungi. They can also bind to specific proteins, interfere with the normal function of proteins, or activate or inhibit the activity of proteins, thereby achieving antibacterial effects. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0029] (1) Aminated silica, methyl 3-formyl-4-hydroxybenzoate and ethanol were mixed uniformly in a mass ratio of 1:1:10, stirred at 200 rpm for 20 min, filtered, washed, and dried at 70°C for 6 h to obtain pre-modified silica; pre-modified silica, deionized water and sodium hydroxide were mixed in a mass ratio of 1:5:0.08, stirred at 200 rpm for 20 min, filtered, washed, and dried at 80°C for 10 h to obtain modified silica;
[0030] (2) Boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate were mixed in a mass ratio of 735:40:1:48, stirred at 200 rpm and 24°C for 22 hours, filtered the filtrate, and dried to obtain boric acid ester; boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile were mixed evenly in a molar ratio of 1:2:6:0.01, stirred at 68°C and 200 rpm for 3 hours, and dried to obtain a self-healing monomer;
[0031] (3) The aldehyde mixture was uniformly added to the ammonia mixture within 8 minutes, reacted at 24°C and 25 rpm for 5 hours, and vacuum dried at 55°C for 4 hours to obtain an organosilicon polymer; the organosilicon polymer and modified silica were stirred at 200 rpm for 20 minutes to obtain an organosilicon polymer material.
[0032] Example 2
[0033] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0034] (1) Aminated silica, methyl 3-formyl-4-hydroxybenzoate and ethanol were mixed uniformly in a mass ratio of 1:1:11, stirred at 250 rpm for 25 min, filtered, washed, and dried at 75°C for 7 h to obtain pre-modified silica; pre-modified silica, deionized water and sodium hydroxide were mixed in a mass ratio of 1:6:0.09, stirred at 250 rpm for 25 min, filtered, washed, and dried at 85°C for 11 h to obtain modified silica;
[0035] (2) Boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate were mixed in a mass ratio of 740:41:1:50, stirred at 250 rpm and 25°C for 24 h, filtered the filtrate, and dried to obtain boric acid ester; boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile were mixed evenly in a molar ratio of 1:2:7:0.015, stirred at 70°C and 250 rpm for 3.5 h, and dried to obtain a self-healing monomer;
[0036] (3) The aldehyde mixture was uniformly added to the ammonia mixture within 9 minutes, reacted at 25°C and 30 rpm for 6 hours, and vacuum dried at 60°C for 5 hours to obtain an organosilicon polymer; the organosilicon polymer and modified silica were stirred at 250 rpm for 25 minutes to obtain an organosilicon polymer material.
[0037] Example 3
[0038] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0039] (1) Aminated silica, methyl 3-formyl-4-hydroxybenzoate and ethanol were mixed uniformly in a mass ratio of 1:1:12, stirred at 300 rpm for 30 min, filtered, washed, and dried at 80°C for 8 h to obtain pre-modified silica; pre-modified silica, deionized water and sodium hydroxide were mixed in a mass ratio of 1:7:0.1, stirred at 300 rpm for 30 min, filtered, washed, and dried at 90°C for 12 h to obtain modified silica;
[0040] (2) Boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate were mixed in a mass ratio of 745:42:1:52, stirred at 300 rpm and 26°C for 26 hours, filtered the filtrate, and dried to obtain boric acid ester; boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile were mixed evenly in a molar ratio of 1:2:8:0.02, stirred at 72°C and 300 rpm for 4 hours, and dried to obtain a self-healing monomer;
[0041] (3) The self-healing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, methanol, oxalic acid and glacial acetic acid were mixed uniformly in a mass ratio of 4-6:30-40:3-5:235-239:0.6-0.7:5-6 to obtain an ammonia mixture; the aldehyde mixture was uniformly added to the ammonia mixture within 10 minutes, reacted at 26°C and 35 rpm for 7 hours, and vacuum dried at 65°C for 6 hours to obtain an organosilicon polymer; the organosilicon polymer and modified silica were stirred at 300 rpm for 30 minutes to obtain an organosilicon polymer material.
[0042] Comparative Example 1
[0043] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0044] (1) Boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate were mixed in a mass ratio of 740:41:1:50, stirred at 250 rpm and 25°C for 24 hours, filtered the filtrate, and dried to obtain boric acid ester; boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile were mixed evenly in a molar ratio of 1:2:7:0.015, stirred at 70°C and 250 rpm for 3.5 hours, and dried to obtain a self-healing monomer;
[0045] (2) The aldehyde mixture was uniformly added to the ammonia mixture within 9 minutes, reacted at 25°C and 30 rpm for 6 hours, and vacuum dried at 60°C for 5 hours to obtain an organosilicon polymer; the organosilicon polymer and nano-silicon dioxide were stirred at 250 rpm for 25 minutes to obtain an organosilicon polymer material.
[0046] Comparative Example 2
[0047] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0048] (1) Boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate were mixed in a mass ratio of 740:41:1:50, stirred at 250 rpm and 25°C for 24 hours, filtered the filtrate, and dried to obtain boric acid ester; boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile were mixed evenly in a molar ratio of 1:2:7:0.015, stirred at 70°C and 250 rpm for 3.5 hours, and dried to obtain a self-healing monomer;
[0049] (2) The aldehyde mixture was uniformly added to the ammonia mixture within 9 minutes, reacted at 25°C and 30 rpm for 6 hours, and vacuum dried at 60°C for 5 hours to obtain an organosilicon polymer material.
[0050] Comparative Example 3
[0051] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0052] (1) Aminated silica, methyl 3-formyl-4-hydroxybenzoate and ethanol were mixed uniformly in a mass ratio of 1:1:11, stirred at 250 rpm for 25 min, filtered, washed, and dried at 75°C for 7 h to obtain pre-modified silica; pre-modified silica, deionized water and sodium hydroxide were mixed in a mass ratio of 1:6:0.09, stirred at 250 rpm for 25 min, filtered, washed, and dried at 85°C for 11 h to obtain modified silica;
[0053] (2) 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, methanol, oxalic acid and glacial acetic acid were mixed in a mass ratio of 35:4:27:0.65:5.5 to obtain an ammonia mixture. The aldehyde mixture was uniformly added to the ammonia mixture within 9 minutes, reacted at 25°C and 30 rpm for 6 hours, and vacuum dried at 60°C for 5 hours to obtain an organosilicon polymer. The organosilicon polymer and modified silica were stirred at 250 rpm for 25 minutes to obtain an organosilicon polymer material.
[0054] Comparative Example 4
[0055] A method for preparing a modified organosilicon polymer material mainly comprises the following preparation steps:
[0056] (1) Aminated silica, methyl 3-formyl-4-hydroxybenzoate and ethanol were mixed uniformly in a mass ratio of 1:1:11, stirred at 250 rpm for 25 min, filtered, washed, and dried at 75°C for 7 h to obtain pre-modified silica; pre-modified silica, deionized water and sodium hydroxide were mixed in a mass ratio of 1:6:0.09, stirred at 250 rpm for 25 min, filtered, washed, and dried at 85°C for 11 h to obtain modified silica;
[0057] (2) Dimethyldimethoxysilane, trimethylmethoxysilane, deionized water and concentrated hydrochloric acid with a mass fraction of 36-38% were mixed in a mass ratio of 8:2:25:2, stirred at 250 r / min for 30 min, heated to 55°C, and continued to react with stirring for 3 h. Sodium carbonate was added to adjust the pH to neutral, stirred for 20 min, cooled to room temperature, washed with deionized water for 4 times, separated, the water phase was removed, and vacuum dried at -5°C for 24 h to obtain an organosilicon polymer; the organosilicon polymer and modified silicon dioxide were stirred at 250 rpm for 25 min to obtain an organosilicon polymer material.
[0058] Test Example 1
[0059] Antimicrobial testing
[0060] Antibacterial performance test: completed in accordance with standard GB / T21866-2008, the tested bacteria include Staphylococcus aureus and Escherichia coli. The results are shown in Table 1. Table 1
[0061]
[0062] From the comparison of the experimental data in Table 1, it can be found that the organosilicon polymer material prepared by the present invention has good antibacterial ability.
[0063] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 1, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 4, which shows that imidazolium ions can exert pharmacological activity by inhibiting the synthesis of DNA and RNA. They can bind to existing enzymes and change the conformation of enzymes, thereby blocking the extension of nucleic acid chains. They can also act as enzyme inhibitors to inhibit specific enzyme activities. In addition, imidazolium ions can interfere with the exchange of substances inside and outside cells by changing the permeability of cell membranes, causing them to lose nutrition and water, and leading to the death of bacteria and fungi. They can also bind to specific proteins, interfere with the normal function of proteins, or activate or inhibit the activity of proteins, thereby achieving antibacterial effects.
[0064] Test Example 2
[0065] Anti-aging and self-repair testing
[0066] Aging test method: The sample is made into a 2cm*5cm*0.5cm sample strip, and the test is placed in a light-oxygen aging test box. A high-pressure mercury lamp is used as the light source for artificial accelerated ultraviolet aging experiments. The ultraviolet radiation intensity on the sample surface is 2200uw / cm 2 , aging temperature is 45℃, aging time is 15d, calculate the tensile fracture retention rate (1), where tensile fracture retention rate (1) = tensile fracture strength after aging treatment / tensile fracture strength before aging treatment * 100%;
[0067] Self-repair test method: The sample is made into a 2cm*5cm*0.5cm strip, and a small cut of 1cm in length and 0.2cm in depth is made on the surface transversely. The sample is placed at 80℃ for 24h, and the tensile fracture retention rate (2) is calculated, where the tensile fracture retention rate (2) = tensile fracture strength after repair / tensile fracture strength before cutting * 100%. The results are shown in Table 2. Table 2
[0068]
[0069] From the comparison of the experimental data in Table 2, it can be found that the organosilicon polymer material prepared in the present invention has good anti-aging and self-repairing capabilities.
[0070] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the elongation-to-break retention rate (1) of Examples 1, 2, 3 is greater than that of Comparative Example 1, indicating that the reaction of amino silicon dioxide and 3-formyl-4-hydroxybenzoic acid methyl ester can generate a structure with the ability to absorb ultraviolet rays, thereby achieving an anti-aging effect;
[0071] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the elongation-to-break retention rate (2) of Examples 1, 2, 3 is greater than that of Comparative Example 3, which indicates that boric acid esters can achieve self-healing effects at high temperatures.
[0072] Test Example 3
[0073] Wear test
[0074] Test method: Test according to standard GB / T1768, the instrument is Taber Type Tester, set the speed to 60r / min, the number of revolutions to 500r, the load to 500g, calculate the mass difference before and after wear, and record it as the wear amount. The results are shown in Table 3. Table 3
[0075]
[0076] From the comparison of the experimental data in Table 3, it can be found that the organosilicon polymer material prepared in the present invention has good wear resistance.
[0077] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 3, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 2, which indicates that nano-silicon dioxide can enhance the wear resistance of the material.
[0078] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a modified organosilicon polymer material, characterized in that: The preparation method of the modified organosilicon polymer material mainly includes the following preparation steps: (1) Mix amino silica, methyl 3-formyl-4-hydroxybenzoate and ethanol in a mass ratio of 1:1:10-12, stir at 200-300 rpm for 20-30 min, filter, wash, and dry at 70-80 ° C for 6-8 h to obtain pre-modified silica; mix pre-modified silica, deionized water and sodium hydroxide in a mass ratio of 1:5-7:0.08-0.1, stir at 200-300 rpm for 20-30 min, filter, wash, and dry at 80-90 ° C for 10-12 h to obtain modified silica; (2) Mix boric acid dispersion, 3,4-dihydroxy-1-butene, deionized water, and magnesium sulfate in a mass ratio of 735-745:40-42:1:48-52, stir at 200-300 rpm and 24-26°C for 22-26 hours, filter the filtrate, and dry to obtain boric acid ester; mix boric acid ester, 3-mercapto-1-propylamine, isopropanol, and azobisisobutyronitrile in a molar ratio of 1:2:6-8:0.01-0.02, stir at 68-72°C and 200-300 rpm for 3-4 hours, and dry to obtain a self-healing monomer; (3) The self-healing monomer, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3-aminopropyltrimethylsilane, methanol, oxalic acid and glacial acetic acid are mixed uniformly in a mass ratio of 4-6:30-40:3-5:235-239:0.6-0.7:5-6 to obtain an ammonia mixed solution; formaldehyde and glyoxal are mixed uniformly in a molar ratio of 1:1 to obtain an aldehyde mixed solution; the aldehyde mixed solution is uniformly added to the ammonia mixed solution within 8-10 minutes, reacted at 24-26°C and 25-35 rpm for 5-7 hours, and vacuum dried at 55-65°C for 4-6 hours to obtain an organosilicon polymer; the organosilicon polymer and modified silica are stirred at 200-300 rpm for 20-30 minutes to obtain an organosilicon polymer material.
2. The method for preparing a modified organic silicon polymer material according to claim 1, characterized in that: The preparation method of the amino silica in step (1) is to uniformly mix nano-silica, 3-aminopropyltrimethoxysilane and isopropanol in a mass ratio of 1:1-2:8-10, stir and react at 85-95°C and 200-300rpm for 5-7h, centrifuge, wash with deionized water for 3-5 times, and dry at 90-100°C for 2-4h.
3. The method for preparing a modified organic silicon polymer material according to claim 2, characterized in that: The specific operation method of the washing in step (1) is to wash with deionized water 3 to 5 times.
4. The method for preparing a modified organic silicon polymer material according to claim 2, characterized in that: The boric acid dispersion in step (2) is prepared by mixing 4-vinylbenzeneboric acid and tetrahydrofuran in a mass ratio of 2-4:69-73 and ultrasonicating for 20-30 minutes.
5. The method for preparing a modified organic silicon polymer material according to claim 2, characterized in that: The specific operation method of the drying in step (2) is vacuum drying at 80-100° C. for 22-24 hours.
Citation Information
Patent Citations
Functionalized nanometer silica with ultraviolet ray absorption function group grafted on surface, and preparation method thereof
CN103849165A
Method for preparing borate bond exchange based self-repairing light-cured reconstructable system
CN109705348A